2016
DOI: 10.1038/bmt.2015.338
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of therapy-related myelodysplasia and AML patients treated with allogeneic hematopoietic cell transplantation

Abstract: The outcome of patients with therapy-related myelodysplasia (t-MDS) or t-AML is very poor. The only curative treatment option implements allogeneic hematopoietic cell transplantation (aHCT); however, long-term follow-up data beyond 5 years are scarce. Here we report on a cohort of 79 consecutive patients with a median age of 58 years (range (r): 20-76) at transplantation and a median follow-up of 7.5 years (r: 0.07-19.0). Only 19 (24.1%) patients were in CR before aHCT. Non-relapse mortality and relapse rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
0
31
1
Order By: Relevance
“…These better outcomes could be secondary to less toxic conditioning regimens leading to better non-relapse mortality. Also, in this study, neither age nor donor type was associated with worse outcomes [104]. Retrospective data from Fianchi et al showed that patients with t-MN who received HCT have better OS than those who did not (58.8 months for allogeneic SCT vs. 12.1 months, P b0.0001) [75].…”
Section: Management Strategies For T-mdsmentioning
confidence: 88%
See 1 more Smart Citation
“…These better outcomes could be secondary to less toxic conditioning regimens leading to better non-relapse mortality. Also, in this study, neither age nor donor type was associated with worse outcomes [104]. Retrospective data from Fianchi et al showed that patients with t-MN who received HCT have better OS than those who did not (58.8 months for allogeneic SCT vs. 12.1 months, P b0.0001) [75].…”
Section: Management Strategies For T-mdsmentioning
confidence: 88%
“…Age greater than 35, poor cytogenetics, disease not in remission at time of HCT, and non-sibling related donor or mismatched unrelated donor were associated with poor outcomes. Data from a more recent but smaller cohort suggests improvement in five year OS, 38% [104]. These better outcomes could be secondary to less toxic conditioning regimens leading to better non-relapse mortality.…”
Section: Management Strategies For T-mdsmentioning
confidence: 89%
“…The authors did not provide mutational data on these patients primarily because it was not being collected routinely in the 1990s and early 2000s. In conclusion, the study by Finke et al 6 show that HCT is feasible and can be used successfully in a fraction of t-MDS/AML patients, and that improved outcomes will require efforts to base transplant decisions on newly available information, some of which will require validation in larger studies or through prospective trials.…”
mentioning
confidence: 99%
“…But based on recent data, the clinical course of t-MN in this primary cancer groups would be closer to de novo disease, thus these cases may do well with non-transplant approaches. The study by Finke et al 6 does not elaborate on the characteristics of the long-term survivors with respect to the site and treatment of primary cancers.…”
mentioning
confidence: 99%
See 1 more Smart Citation